Visual inspection with acetic acid screening use determinants: a systematic literature review - Ayu, Septi; Hadi, Ella Nurlaella (Universitas Gadjah Mada, 2024)
Purpose: In Indonesia, in 2022, of 36,964 cervical cancer cases, 56% ended in death due to cervical cancer. Cervical cancer can be identified at an early stage through routine examinations, allowing for more effective treatment and increasing the chances of cure. The visual inspection of acetic acid (VIA) screening has emerged as a simple, effective, and affordable option. Methods: The research method uses a systematic literature review, carried out using primary studies from PubMed, Proquest, and Google Scholar using the keywords